Belowground drivers of plant diversity - van der Putten, Wim H. (Science (American Association for the Advancement of Science), 2017)
Feedbacks between soil microbes and plants affect the diversity of plant communities Long before Ernst Haeckel coined the term “ecology” in 1866, nature explorers, such as Alexander von Humboldt, observed that vegetation composition changes with climate. However, it still remains unclear what determines the local composition and species richness of vegetation. Understanding the roles of belowground invertebrates and microbes is particularly challenging. On pages 173 and 181 of this issue, respectively, Teste et al. ( 1 ) and Bennett et al. ( 2 ) report field studies that elucidate the role of soil microorganisms as drivers of plant community composition.